Concise synthesis and confirmation of the absolute configurations of naturally occurring bioactive 2,7′-cyclolignans - Nannaphat Chumsri (2022)
A concise asymmetric synthesis of naturally occurring bioactive 2,7′-cyclolignans, namely 4,4′-dihydroxy-3′,5,5′-trimethoxy-2,7′-cyclolignan and 4,4′-dihydroxy-3,3′,5-trimethoxy-2,7′-cyclolignan, possessing the uncommon 8,8′-syn dimethyl stereochemistry and unsymmetrical C-6 units with 7′,8′-anti-orientation is described using a substrate-controlled stereoselective Friedel-Crafts cyclization as the key step. The products were obtained in good yields with high stereoselectivity. The absolute configurations of natural 4,4′-dihydroxy-3′,5,5′-trimethoxy-2,7′-cyclolignan and those of natural 4,4′-dihydroxy-3,3′,5-trimethoxy-2,7′-cyclolignan were assigned as (7′S,8S,8′S) and (7′R,8R,8′R), respectively, based on the experimental circular dichroism (CD) spectra of the corresponding synthesized compounds.